Loh Batu Yang Baru, Siapakah Penulisnya? Analisis terhadap Keluaran 34:1, 28 - Rubyantara Jalu Permana; Sonny Eli Zaluchu (Sekolah Tinggi Teologi Baptis Indonesia, 2020)
The literal differences found in the text of Exodus 34 verses 1 and 28 can trigger accusations of Bible inconsistency. In fact, in the Christian view, the Bible is a book that cannot be wrong or inner. Evangelical Christian beliefs assert that the Bible contains God's word and God's word itself. If there are differences and inconsistencies in the Bible, is that an indicator to deduce the low credibility of truth in the Christian scriptures? This study aims to answer that question through a hermeneutic and theological analysis of the differences in texts in Exodus 34 or 1 and verse 28, about who actually wrote the two new tablets. God as referred to verse 1 or Moses as read in verse 28. In addition to conducting text analysis, the author also uses the source approach and theological concepts. As a result, verse 28 actually legitimizes verse 1 that God himself wrote the law. This perspective also confirms that the search for the meaning of texts in context does not merely involve a grammatical approach.